Gastric form of alpha chain disease. Issue 6 (June 1986) - Coulbois, J; Galian, P; Galian, A; Couteaux, B; Danon, F; Rambaud, J
Abstract : A case of alpha chain disease, involving the stomach only, is reported in an Algerian man suffering from epigastric pains. Upper digestive tract fibreoptic endoscopy showed two antral ulcers and an ulcerative gastritis pattern, which promptly disappeared with cimetidine treatment. Antral biopsies at a distance from the ulcers, but not of the ulcer crater itself, disclosed a dense infiltration of antral lamina propria by mature or sometimes atypical plasma cells. On transmural surgical antral biopsy, the infiltrate spread to the superficial part of the submucosa. No other localisation of the disease was found in spite of multiple biopsies obtained by endoscopy, with a peroral capsule and during staging laparotomy. The alpha chain disease protein was absent from serum and urine, but found in the gastric juice and in the cytoplasma of the cellular infiltrate (alpha 1 subclass). A complete clinical, endoscopic, histological and immunological remission was observed after a six months' course of oral tetracycline.